2020
DOI: 10.1038/s41419-020-03155-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR-18a sensitizes chondrocytes to anticytokine therapy to prevent osteoarthritis progression

Abstract: Inflammation participates in the development of OA and targeting inflammatory signaling pathways is a potential strategy for OA treatment. IL-1β is one of the most important inflammatory factors to trigger the activation of NF-κB signaling and accelerate OA progression, whereas OA patients could hardly benefit from inhibiting IL-1β in clinic, suggesting the importance to further explore the details of OA inflammation. We here showed that expression of miR-18a in chondrocytes was specifically induced in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The expression of miR-18a is induced by IL-1β and accelerates the progression of osteoarthritis [ 19 ]. IL-1β is a pivotal cytokine in the inflammatory gout cascade; our results are consistent when we consider differences between groups where patients with hyperuricemia and gout had significantly higher levels of miR-18a; however, we did not find any difference for gout attack patients or a direct correlation between IL-1β and miR-18a levels.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-18a is induced by IL-1β and accelerates the progression of osteoarthritis [ 19 ]. IL-1β is a pivotal cytokine in the inflammatory gout cascade; our results are consistent when we consider differences between groups where patients with hyperuricemia and gout had significantly higher levels of miR-18a; however, we did not find any difference for gout attack patients or a direct correlation between IL-1β and miR-18a levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miRNA is differently expressed in the cartilage of OA patients compared with the normal cartilage. Some miRNAs (e.g., miR-9, miR-18a, miR-22, miR-60) are up-regulated, [ 141 144 ], while others (e.g., miR-27, miR-140, miR-146, 149-5p, miR-199a, miR-miR-602, miR-608) are down-regulated [ 145 150 ]. The changes influence various target genes and numerous physiological mechanisms, including lipid metabolism, matrix degradation, inflammation, and chondrocytes differentiation.…”
Section: Epigenetic Therapy For Age-related Skeletal Diseasesmentioning
confidence: 99%
“…IL‐1β plays a key role in the occurrence and development of OA, which was seemed to be associated with cartilage destruction. 32 It is one of the most significant mediators of cartilage degeneration and joint inflammation. 33 IL‐1β can stimulate chondrocytes to induce the expression of MMPs, ADAMTSs and other catabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that MSC-Exo treatment was expected to replace MSC administration and plays a cartilage-protective role in the in vivo OA model.Furthermore, we constructed an in vitro OA model by culturing chondrocytes in IL-1β-contained medium to mimic inflammation environment in arthritis. IL-1β plays a key role in the occurrence and development of OA, which was seemed to be associated with cartilage destruction 32. It is one of the most significant mediators of cartilage degeneration and joint inflammation 33.…”
mentioning
confidence: 99%